Kafka, Benjamin, Derrida: On Violence, Law and Justice - Khujadze, Zhiron (Journal of Law, 2023)
Kafka’s parable “Before the Law” tells us about the countryman who spends his whole life in front of the law’s gate and aims futilely to gain access to it. This article is devoted to the main question expressed as follows: why can’t the man attain his aim? Wording the question is already an interpretation which in Kafka’s world is not completed by “solving”. And philosophers of “irresoluble” are Walter Benjamin and Jacques Derrida. They read Kafka (his literature and his personality) and help the man from the country, which requires analysing the connections and relations between the law (das Gesetz, la loi) and violence, law (das Recht, le droit) and religious teachings, the law and its origins, law and justice.